Benjamin L.C. Wailes diary excerpt - Wailes, Benjamin L. C. (Benjamin Leonard Covington), 1797-1862.
Transcript of Wailes's diary entry (1859 July 25) describing a visit to Peter Force and their discussion of books and manuscripts relating to American and Mississippi history.
Typewritten transcript.
Planter and educator of Mississippi.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Force, Peter, -- 1790-1868.; Mississippi -- Historiography; United States -- Historiography; Educators; Plantation owners